Overview of the breadth of bacterial resistance development within the framework of antibiotics and antimicrobial peptides - Rajendra Kr Roy; Raju Biswas; Analabha Roy; Rahul Chandra; Rajdeep Shaw; Arun Kumar Shaw; Rajib Bandopadhyay (The Microbe, 2025)
The challenge posed by bacterial infections has intensified significantly. Antibiotics, once considered revolutionary treatments, are now frequently ineffective against resistant pathogens, known as superbugs, which threaten to result in global economic losses of trillions of dollars in the coming years. The inappropriate prescription of antibiotics and their excessive use in both clinical and nonclinical settings have exacerbated this problem, leading to increased mortality rates and increased healthcare costs. As the efficacy of conventional treatments decreases, novel strategies are being developed. Fortunately, researchers are exploring new approaches, including antimicrobial peptides (AMPs), which demonstrate significant potential to address bacterial resistance. AMPs are small, amphiphilic molecules derived from precursor peptides through processes such as proteolytic activation, ribosomal translation, or non-ribosomal peptide synthesis. They exhibit broad-spectrum antimicrobial properties against a variety of pathogens, including bacteria, fungi, parasites, and viruses. Due to their ability to interact with multiple sites on bacterial membranes, AMPs present a promising alternative to traditional antibiotics, which often act on specific targets and contribute to resistance development. Research has shown that AMPs originate from various sources, including bacteria, plants, and animals. Notable examples of bacterial-derived AMPs include nisin, which is used as a natural food preservative, and polymyxins, which are used as broad-spectrum antimicrobials. Furthermore, peptides engineered from wasp venom have been shown to possess antimicrobial properties while minimizing toxicity to human cells. Recent findings also include “encrypted peptides” found in human plasma, which exhibit potential antimicrobial activity by targeting bacterial membranes. In addition, the combination of AMPs with traditional antibiotics can significantly enhance antimicrobial efficacy and reduce the likelihood of developing bacterial resistance. This article underscores the promising potential of AMPs as innovative solutions to address the antibiotic resistance crisis, thus paving the way for new therapeutic applications.